Comparative study of mucinous and non-mucinous appendiceal neoplasms with peritoneal dissemination treated by cyoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC). Issue 5 (May 2021) - Garach, Niharika Rajan; Kusamura, Shigeki; Guaglio, Marcello; Bartolini, Valentina; Deraco, Marcello; Baratti, Dario
Abstract: Background: Appendiceal non-mucinous neoplasms (AnMN) are rare and poorly understood malignancies with no standard treatment. Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) is largely used to treat peritoneal disseminations from appendiceal mucinous neoplasms (AMN), but its role with AnMN is unclear. Methods: A prospective database of 315 patients with advanced appendiceal primaries undergoing CRS/HIPEC during 1996–2020 was reviewed. Baseline characteristics, operative and long-term outcomes of AnMN were compared with those of AMN. AMN were categorized according to PSOGI classification into high-grade, low-grade, and acellular mucin (AC), based on peritoneal disease histology. Results: Twenty-three patients (7.3%) with goblet cell carcinoma (GCC; n = 9), intestinal-type adenocarcinoma (ITAC; n = 12), and mixed adeno-neuroendocrine carcinoma (MANEC; n = 2) were identified. AnMN patients were more likely to be males (P = 0.006), have preoperative systemic chemotherapy (P = 0.001), grossly incomplete CRS (P = 0.001), and nodal metastases (P = 0.001), but not systemic relapse after CRS/HIPEC (P = 0.133). Median follow-up was 25.1 months (range 0.8–77.3) for AnMN, and 80.9 months (range 0.1–279.2) for AMN. Median overall survival was 24.0 months for AnMN, 66.2 months for high-grade AMN (P = 0.015), 160.0 months for low-grade ANM (P = 0.001), and not reached for AC (P = 0.001). Among AnMN patients, median survival was 23.4 months for GCC, 38.7 months for ITAC, 20.3 months for MANEC (P = 0.855). In the overall series, histological subtype (P = 0.001), incomplete cytoreduction (P = 0.001), and positive lymph-nodes (P = 0.003) correlated with poorer survival at multivariate analysis. Conclusions: AnMN share with AMN a predominant local-regional dissemination pattern, but prognosis after CRS/HIPEC is worse. This strategy needs to be carefully considered for AnMN. patients. Highlights: Appendiceal non-mucinous neoplasms show a predominant peritoneal metastatic pattern Histologic subtype impacts prognosis of appendiceal neoplasms with peritoneal spread Survival of goblet cell and intestinal-type carcinomas is worse than mucinous tumours Only selected goblet cell and intestinal-type carcinomas are amenable to surgery